FAKTOR-FAKTOR YANG MEMPENGARUHI KESEDIAAN MEMBAYAR KONSUMEN TERHADAP KOPI FAIR TRADE - vista uli sihombing; Anna Fariyanti; Rachmat Pambudy (JURNAL AGRIBISAINS, 2022)
Coffee drink products that have a fair trade label tend to have a higher price than non-fair trade label coffee drinks, so that some consumers perceive that coffee is an expensive product. This study aims to determine how much consumers are willing to pay for coffee drinks labeled as fair trade and the factors that influence it. This study uses primary data from an online survey of 120 respondents in North Sumatra Province who have purchased coffee drinks with a fair trade label. Data analysis used logistic regression analysis. The results show that the majority of consumers are willing to pay more for coffee drinks labeled as fair trade with an increase of 5-10% from the current product price. The factors that influence the willingness to pay for coffee drinks labeled as fair-rade are age, education, marital status and coffee quality.